Identification of cereulide producing Bacillus cereus by MALDI-TOF MS. (September 2019) - Ulrich, Sebastian; Gottschalk, Christoph; Dietrich, Richard; Märtlbauer, Erwin; Gareis, Manfred
Abstract: The Bacillus ( B .) cereus group consists of nine recognized species which are present worldwide. B. cereus play an important role in food-borne diseases by producing different toxins. Yet, only a small percentage of B. cereus strains are able to produce the heat stable cereulide, the causative agent of emetic food poisoning. To minimize the entry of emetic B. cereus into the food chain, food business operators are dependent on efficient and reliable methods enabling the differentiation between emetic and non-emetic strains. Currently, only time-consuming cell bioassays, molecular methods and tandem mass spectrometry are available for this purpose. Thus, the aim of the present study was to establish a fast and reliable method for the differentiation between emetic/non-emetic strains by MALDI-TOF MS. Selected strains/isolates of the B. cereus group as well as other Bacillus spp. (total n = 121) were cultured on sheep blood agar for 48 h before analysis. Subsequently, the cultures were directly analyzed by MALDI-TOF MS without prior extraction steps. The samples were measured in the mass range of m/z 800–1800 Da. Using ClinProTools 3.0 statistical software and Flex analysis software (Bruker Daltonics GmbH, Bremen, Germany), a differentiation between emetic/non-emetic isolates was possible with a rate of correct identification of 99.1% by means of the evaluation of two specific biomarkers ( m/z 1171 and 1187 Da). Highlights: Fast/reliable MALDI-TOF MS method for differentiation of emetic/non-emetic B. cereus . Directly analyzed by MALDI-TOF MS without prior extraction steps (direct smear). Differentiation of emetic/non-emetic B. cereus with 99.1% correct identification. Biomarkers for differentiation of emetic/non-emetic B. cereus ( m/z 1171 and 1187 Da).